Nutrition in the prevention and treatment of endometriosis: A review - Barnard, Neal D.; Holtz, Danielle N.; Schmidt, Natalie; Kolipaka, Sinjana; Hata, Ellen; Sutton, Macy; Znayenko-Miller, Tatiana; Hazen, Nicholas D.; Cobb, Christie; Kahleova, Hana (Frontiers in Nutrition, 2023)
Endometriosis is characterized by the presence of endometrial tissues outside the uterine lining, typically on the external surface of the uterus, the ovaries, fallopian tubes, abdominal wall, or intestines. The prevalence of endometriosis in North America, Australia, and Europe is ~1–5% in women of reproductive age. Treatment options for endometriosis are limited. While over-the-counter medications may be used to reduce acute pain, hormonal treatments are common and may interfere with fertility. In more severe cases, laparoscopic excision procedures and even hysterectomies are used to treat the pain associated with endometriosis. Nutritional interventions may be helpful in the prevention and treatment of endometriosis and associated pain. Reducing dietary fat and increasing dietary fiber have been shown to reduce circulating estrogen concentrations, suggesting a potential benefit for individuals with endometriosis, as it is an estrogen-dependent disease. Meat consumption is associated with greater risk of developing endometriosis. Anti-inflammatory properties of plant-based diets may benefit women with endometriosis. Additionally, seaweed holds estrogen-modulating properties that have benefitted postmenopausal women and offers potential to reduce estradiol concentrations in pre-menopausal women. Furthermore, consumption of vitamin D has been shown to reduce endometrial pain via increased antioxidant capacity and supplementation with vitamins C and E significantly reduced endometriosis symptoms, compared with placebo. More randomized clinical trials are needed to elucidate the role of diet in endometriosis.